2018
DOI: 10.1186/s12884-018-1937-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequela of female genital mutilation on birth outcomes in Jijiga town, Ethiopian Somali region: a prospective cohort study

Abstract: BackgroundIn Ethiopia, female genital mutilation (FGM) remains a serious concern and has affected 23.8 million women and girls, with the highest prevalence in Somali regional state. Even though FGM is reported to be associated with a range of obstetric complications, little is known about its effects on childbirth in the region. Therefore, the objective of this study was to test the hypothesis that FGM is a contributing factor to the increased risk of complication during childbirth.MethodsFacility based cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 13 publications
1
44
4
Order By: Relevance
“…However, FGM is a practice associated with adverse health outcomes, such as poor mental health, psychological and emotional disturbance and persistent lower urinary tract symptoms, bacterial vaginosis and dyspareunia, all of which need better documentation, appropriate treatment and further research [3,26,27]. As discussed earlier, FGM is also associated with adverse maternal outcomes such as obstructed labour, post-partum bleeding and the need for emergency caesarean section [9].…”
Section: Plos Onementioning
confidence: 99%
“…However, FGM is a practice associated with adverse health outcomes, such as poor mental health, psychological and emotional disturbance and persistent lower urinary tract symptoms, bacterial vaginosis and dyspareunia, all of which need better documentation, appropriate treatment and further research [3,26,27]. As discussed earlier, FGM is also associated with adverse maternal outcomes such as obstructed labour, post-partum bleeding and the need for emergency caesarean section [9].…”
Section: Plos Onementioning
confidence: 99%
“…This study commensurates the findings from a narrative review of psychosexual consequences and a meta-analysis study on Nigerian women based on their psychosocial analysis. The former posited that women with FGM are more prone to developing psychological disorders such as phobia, anxiety, somatization, self-esteem, and post-traumatic stress disorder and equally physiological problem in respect to being sexually stimulated, while the latter revealed that FGM creates psychological problems, sexual abnormalities, and unhappiness in marriage [48,49].…”
Section: Consequences Of Female Genital Mutilation In Africamentioning
confidence: 99%
“…In Ethiopia, the prevalence of FGM was 80% according to Ethiopia Demographic Health Survey (EDHS) 2000 [ 12 ], 75% according to EDHS 2005 [ 13 ], and 70.8% according to EDHS 2016 [ 14 ]. Concerning regional states in Ethiopia, the highest prevalence of FGM was found in Afar, Somali, Hadya, and Wolayta but less prevalent in Gambella and Tigray [ 13 , 15 ] . According to EDHS 2005, the prevalence of FGM in the Amhara region was 74% [ 16 ] while the cross-sectional study in Lejet kebele, Dembecha woreda, Amhara region in 2014 report that 94% women and 34.2% of under five children were circumcised [ 17 ].…”
Section: Introductionmentioning
confidence: 99%